Suplementos proteicos com adição de levedura para bovinos consumindo forragem de baixa qualidade - Teodoro, Ana Lúcia (2014)
Two experiments were carried out at the Fazenda Experimental de Iguatemi (FEI) in the Universidade Estadual de Maringá, from June to October 2012. The first experiment was conducted to evaluate the use of yeast in a protein supplements and effects on nutrient intake, partial and total nutrient digestibility, ruminal fermentation, microbial synthesis and serum parameters in cattle fed low quality forage. There were used five Holstein steers, with mean body weight of 485±60 kg and implanted with ruminal and duodenal cannulas. The experimental design was a 5x5 Latin square design. The animals received chopped straw of Brachiaria humidicola cv. Llanero ad libitum and a protein supplement containing 50% crude protein (CP) fed on the basis of 0.15% of body weight. The experimental treatments consisted of yeast inclusion in the protein supplement as following: 0, 0.2, 0.4, 0.6 and 0.8% of yeast (Saccharomyces cerevisiae - NCYC 996-10 billion CFU/g, LeSaffre®). It was observed a quadratic effect (p<0.05) for duodenal flow of organic matter (OM) and total carbohydrates (CHO) and a decreasing linear effect for ruminal degradability of CP (p=0.04). For duodenal flow of DM, CP and neutral detergent fiber (NDF) and ruminal degradation of OM and CHO, it was found that there was a linear and quadratic tendency effect (p<0.10), while for the intestinal digestion of CP there was only a linear tendency effect (p=0.09). All the other parameters evaluated were not influenced by treatments (p>0.05). The intake of dry matter and nutrients decreased 3% with the inclusion of yeast as well as duodenal flow and fecal output that were on average 10.1 and 7.3% lower, respectively. The coefficient of degradability for DM, NDF, OM and CHO increased 13.8; 5.8; 11.8 and 8.5% with the inclusion of yeast in the protein supplement. Total tract digestibility of dry matter and total digestible nutrients (TDN) increased 4.5 % and 4.2 %, respectively. The second experiment was conducted to evaluate the use of yeast in a protein supplement for heifers fed low quality forage and its effects on intake, weight gain and feed efficiency. Forty crossbred heifers with approximately 18 months of age and an average initial weight of 247±40 kg were assigned to 5 treatments in a completely randomized design. The animals were fed chopped straw of Brachiaria humidicola cv.Llanero ad libitum and a protein supplement 50 % CP. Treatments consisted of the use of yeast (Saccharomyces cerevisiae - NCYC 996 -10 billion CFU/g, LeSaffre®) in the protein supplement as following: 0, 0.2 %, 0.4%, 0.6 % and 0.8 % of inclusion. Dry matter intake was 6.1 kg animal-1.d-1, average daily gain was 206 g d-1 and feed efficiency of 0.04 kg kg-1. Heifers receiving yeast showed increase of 5.8% on intake, 34% on daily gain and 25% on feed efficiency compared to control, however there was no significant difference (p>0.05) due to treatments. The average gain of 10 kg in heifers receiving yeast in the protein supplement may be considered satisfactory since the diet was based in grass straw. The use of yeast as an additive may improve fiber digestibility in the periods when the available forage is of low quality.